(untitled) (Latakia University Journal -Medical Sciences Series, 2021)
Aim: Studying the effect of diabetes and glycemic control on the primary failure of the radio-cephalic fistula prepared for hemodialysis in addition to studying the effect of the other pathological and pharmacological factors on the results.Methods: A Prospective comparative study in which 53 patients with end-stage renal insufficiency had a radio-cephalic fistula. The patients were divided into two groups according to the presence of diabetes, Diabetic patients were divided into two groups according to glycemic controlling by measuring Glycated hemoglobin (HbA1c) (controlled: HBA1C<7%, uncontrolled: HBA1C≥7%). The patients were followed up for three months after surgery and the outcome of the procedure was evaluated in terms of maturity or primary failure.Results: Our study comprised of 53 patient(60.4% males and 39.6% females). The number of diabetic patients was 29, including 16 non-glycemic controlled patients and 13 glycemic controlled .15 patients had a history of primary AVF failure (28.3%), including 12 diabetic patients (80%) compared to 3 non-diabetic patients (p value = 0.02).primary Failure also occurred in 9 patients with uncontrolled diabetes (75%)against 3 patients with controlled diabetes (p value = 0,03). The failure rate for patients with associated peripheral vascular disease was 46.7%, while the maturity rate was 21.1% (p value = 0.03). The failure rate of fistula with Antiplatelet drug usage was 33.3%, while the maturity rate was 57.9. % (p value = 0,04).Conclusions: The presence of diabetes in general and poor glycemic control in particular is associated with an increase in the primary failure rates of the radio-cephalic fistula, and the presence of associated peripheral vascular disease played a role in increasing failure rates, while anti-platelet usage played a role in increasing the rates of maturation.